Do State-Owned Banks Promote Growth? Cross-Country Evidence for Manufacturing Industries - Arturo Galindo; Alejandro Micco (Inter-American Development Bank, Research Department, 2003)
This paper tests the efficiency of different structures of bank ownership in terms of its ability to target manufacturing sectors in need of credit. We find that state- owned banks do not play a significant role in the development of industries that rely more on external finance and/or that have less tangible assets to pledge as collateral.
Keywords: 330; Öffentliche Bank; Bank; Eigentümerstruktur; Kreditgeschäft; Schätzung; Welt